Volume 1: Aircraft Engine; Marine; Turbomachinery; Microturbines and Small Turbomachinery 2000
DOI: 10.1115/2000-gt-0446
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Airfoil Scaling on the Predicted Unsteady Loading on the Blade of a 1 and 1/2 Stage Transonic Turbine and a Comparison With Experimental Results

Abstract: In this study, two time-accurate Navier-Stokes analyses were obtained to predict the first-vane/first-blade interaction in a 1 and 1/2-stage turbine rig for comparison with measurements. In the first computation, airfoil scaling was applied to the turbine blade to achieve periodicity in the circumferential direction while modeling 1/18 of the annulus. In the second, 1/4 of the wheel was modeled without the use of airfoil scaling. For both simulations the predicted unsteady pressures on the blade were similar i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 0 publications
2
15
0
Order By: Relevance
“…The blade geometries were then scaled to fit the cyclical sector model. Although this procedure was found to be adequate for aerodynamic performance predictions, it was found through further investigations [9] that "scaling" is not accurate enough for structural forced response analyses because of the phase difference in local unsteady pressures acting on the blade surface. Therefore, the turbine was to be modeled with the true blade ratios meaning, in this particular case of prime numbers of blades, a full 360 0 CFD model approximately 7 times larger in grid size.…”
Section: B J-2x Fuel Turbine Analysesmentioning
confidence: 99%
“…The blade geometries were then scaled to fit the cyclical sector model. Although this procedure was found to be adequate for aerodynamic performance predictions, it was found through further investigations [9] that "scaling" is not accurate enough for structural forced response analyses because of the phase difference in local unsteady pressures acting on the blade surface. Therefore, the turbine was to be modeled with the true blade ratios meaning, in this particular case of prime numbers of blades, a full 360 0 CFD model approximately 7 times larger in grid size.…”
Section: B J-2x Fuel Turbine Analysesmentioning
confidence: 99%
“…Unfortunately, no comparisons between their predictions and the experimental data were shown for the downstream second vane. The current investigation was performed as a validation of the TFLO (Yao et al, 2001) procedure, an independent verification of the results of Clark et al (2000), as well as a grid-refinement study to see if grid-density was a major factor in prediction accuracy. As described below, the computational grid density used in the current investigation was approximately three times greater than that used by Clark et al (2000).…”
Section: Figurementioning
confidence: 99%
“…Significant experimental and numerical research has been performed over the last several years on highlighting and understanding the unsteady aerodynamics of multi-stage turbomachinery (e.g., Reinmoller et al, 2001;Arnone et al, 2001;Gombert and Hohn, 2001;Dorney et al, 2001;Clark et al, 2000;Busby et al, 1998;Rao et al, 1994;Chen et al, 1994;Sharma et al, 1992;Takahashi and Ni, 1991;Giles, 1990;Jorgenson and Chima, 1990;Rai, 1987;Dring et al, 1992). Much of this work has focused on quantifying the unsteady flow field resulting from the interaction between rotors and stators in terms of aerodynamic performance and airfoil surface unsteady pressure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Clark 4 showed that the fundamental and first harmonic of the pressure make up over 90% of the pressure envelope over most of the surface.…”
Section: % Spanmentioning
confidence: 99%